1987
DOI: 10.1016/0027-5107(87)90275-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of DNA loop length in nontransformed and transformed hamster cells

Abstract: Comparative analysis of DNA loop length in nontransformed and transformed hamster cells Linskens, Maarten; Eijsermans, Anneline; Dijkwel, Peter A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…The occurrence of MARs at 70-to 120-kb intervals within the DHFR locus agrees well with estimates for the average size of DNA loops in mammalian cells (6,21,34). In several studies, it has been suggested that chromosomal loops correspond to replicons on the basis of their similar average sizes and proposed mechanisms for DNA replication (e.g., 6, 34).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The occurrence of MARs at 70-to 120-kb intervals within the DHFR locus agrees well with estimates for the average size of DNA loops in mammalian cells (6,21,34). In several studies, it has been suggested that chromosomal loops correspond to replicons on the basis of their similar average sizes and proposed mechanisms for DNA replication (e.g., 6, 34).…”
Section: Discussionsupporting
confidence: 78%
“…DNA concentrations were additionally determined by a fluorimetric assay based on Hoechst staining (20). In a typical matrix preparation digested with an enzyme such as EcoRI, 4% of the total DNA remains attached to the matrix, which is close to the figure one would expect if the enzyme cuts every 4 kb on average and if chromosomal loops are 80 to 100 kb in length (6,21,36). Incubation with the combination EcoRI-HindIII-BamHIPvuII reduced this proportion to 1 to 2%.…”
Section: Methodsmentioning
confidence: 88%
“…In Figure 5, we propose a model of chromatin organization of the studied 167 kb genomic region containing p53 and neighboring genes. Our results are quite surprising, since the average loop size is believed to be smaller in cancer cells as compared to that in normal controls [Linskens et al, 1987;Oberhammer et al, 1993]. Considering the importance of the TP53 tumor suppressor, it is possible that the studied region is contextually dependent on the state of the cell.…”
Section: Discussionmentioning
confidence: 47%
“…Rearrangement of DNA loops occurs during development when the loop size increases in somatic cells [Buongiorno-Nardelli et al, 1982;Vassetzky et al, 2000a]. Conversely, the average loop size decreases in transformed cells [Linskens et al, 1987] and in several human cancer cell lines in which it was found to be smaller than in their non-transformed counterparts [Oberhammer et al, 1993]. This may reflect a reversal in the differentiated state of the normal cells.…”
mentioning
confidence: 89%
“…Rearrangement of DNA loops was also found in transformed BHK21 cells where the average size of loops was found to decrease [Linskens et al, 1987]. Additionally, the loop size in several human cancer cell lines was found to be ca.…”
Section: Loop Modification During Development and Cancermentioning
confidence: 74%